1931 Cal. Stat. 2317 - (:unkn) unknown (My University, 1931)
Ch. 1098, §9: Required every person in the business of selling, leasing, or otherwise transferring a pistol, revolver, or other firearm capable of being concealed, shall enter the time of sale, date of sale, name of the salesman, place it was sold, the make, model, manufacturer's number, caliber, and other marks of identification on such pistol, revolver, or other firearm.
Keywords: TRANSFER